Predictors of pain-related functional impairment among people living with HIV on long-term opioid therapy. Issue 4 (3rd April 2021) - Serota, David P.; Capozzi, Christine; Lodi, Sara; Colasanti, Jonathan A.; Forman, Leah S.; Tsui, Judith I.; Walley, Alexander Y.; Lira, Marlene C.; Samet, Jeffrey; del Rio, Carlos; Merlin, Jessica S.
ABSTRACT: People living with HIV (PLWH) have high levels of functional impairment due to pain, also called pain interference. Long-term opioid therapy (LTOT) is commonly prescribed for chronic pain among PLWH. We sought to better understand the predictors of pain interference, measured with the Brief Pain Inventory Interference subscale (BPI-I), among PLWH with chronic pain on LTOT. Using a prospective cohort of PLWH on LTOT we developed a model to identify predictors of increased pain interference over 1 year of follow up. Participants ( n  = 166) were 34% female, 72% African American with a median age of 55 years, and 40% had severe pain interference (BPI-I ≥ 7). In multivariable models, substance use disorder, depressive symptoms, PTSD symptoms, financial instability, and higher opioid doses were associated with increased pain interference. Measures of behavioral health and socioeconomic status had the most consistent association with pain interference. In contrast, the biomedical aspects of chronic pain and LTOT – comorbidities, duration of pain – were not predictive of pain interference. PLWH with chronic pain on LTOT with lower socioeconomic status and behavioral health symptoms have higher risk of pain interference. Addressing the social determinants of health and providing access to behavioral health services could improve patients' pain-related functional status.